2008
DOI: 10.1021/jp8030336
|View full text |Cite
|
Sign up to set email alerts
|

Guanidinium Chloride Molecular Diffusion in Aqueous and Mixed Water−Ethanol Solutions

Abstract: Solutions containing guanidinium chloride (GdmCl), or equivalently guanidine hydrochloride (GdnHCl), are commonly used to denature macromolecules such as proteins and DNA in, for example, microfluidics studies of protein unfolding. To design and study such applications, it is necessary to know the diffusion coefficients for GdmCl in the solution. To this end, we use molecular dynamics simulations to calculate the diffusion coefficients of GdmCl in water and in water-ethanol solutions, for which no direct exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…We have recently studied the linear molecules, carbon monoxide, nitric oxide, and cyanide ion in a water–ethanol mixture. It was found that as the ethanol composition in the mixture increases, the translational diffusion coefficient of neutral molecules also increases, whereas that of the charged ion decreases. , Another important study in the ion–water–ethanol mixture was performed with guanidium chloride (GdmCl) by Gannon et al The fully atomistic simulations showed that with the increase in the concentration of ethanol and the cation Gdm + , the diffusion of the cation decreases . Tembe and co-workers, in their study of magnesium chloride in water–ethanol mixture, showed that with the increase in the ethanol mole fraction, the ion pairing becomes more favorable .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently studied the linear molecules, carbon monoxide, nitric oxide, and cyanide ion in a water–ethanol mixture. It was found that as the ethanol composition in the mixture increases, the translational diffusion coefficient of neutral molecules also increases, whereas that of the charged ion decreases. , Another important study in the ion–water–ethanol mixture was performed with guanidium chloride (GdmCl) by Gannon et al The fully atomistic simulations showed that with the increase in the concentration of ethanol and the cation Gdm + , the diffusion of the cation decreases . Tembe and co-workers, in their study of magnesium chloride in water–ethanol mixture, showed that with the increase in the ethanol mole fraction, the ion pairing becomes more favorable .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, convective and diffusive mass transfer should be reduced in a hydrogel compared to the crowding and free solutions, possibly slowing down dispersal of solutes. It was estimated that guanidinium would diffuse through the gel in 100 min, assuming 1D Fickian diffusion through a 2.2‐mm thick gel, a diffusivity of 6.5 × 10 −6 cm 2 /s in water, and reduction in effective diffusivity of 40% in the hydrogel (Gannon et al, 2008; Zustiak, Boukari et al, 2010). However, the tertiary structure of lysozyme responds rapidly to changes in denaturant concentration (van den Berg et al, 1999), and we suggest that differences in exposure time had minimal impact on lysozyme unfolding as the experiment was conducted for 120 min while it should have taken approximately 100 min for an equilibrium concentration of GuSCN or acrylamide to be reached between the surrounding solution and the gel.…”
Section: Discussionmentioning
confidence: 99%
“…These data were used to determine the permeation coefficient P , which was calculated as 1.1 × 10 -10 m 2 /s. The diffusion coefficient in the solution was about 5 x 10 -10 m 2 /s (Gannon et al, 2008). After 1440 min the concentrations in the feed and permeation chambers became almost equal.…”
Section: Design and Fabrication Of Microchannelsmentioning
confidence: 93%
“…(2). Atomistic molecular dynamics simulations predicted that the diffusivity of GdnHCl depends on the concentration of GdnHCl; for example, diffusivity at 5 M GdnHCl is around one third of that at 1 M GdnHCl (Gannon, Larsson, Greer, & Thompson, 2008). The permeation coefficient, P , used for the microchannel design was modified accordingly.…”
Section: 21measurement Of the Permeation Coefficient Of Gdnhcl Thmentioning
confidence: 99%
See 1 more Smart Citation